A hospital based surveillance system to assess the burden of trauma in KwaZulu-Natal Province South Africa. Issue 1 (January 2016) - Lutge, Elizabeth; Moodley, Nirvasha; Tefera, Aida; Sartorius, Benn; Hardcastle, Timothy; Clarke, Damian
Abstract: Introduction: In response to the ongoing excessive burden of trauma in South Africa the Data Management and Epidemiology Units of the Department of Health in conjunction with a group of trauma specialists developed a number of trauma data variables for inclusion on the routine District Health Information System (DHIS). The aim of this study is to describe the process followed and review the 2012–2014 data. Methodology: The variables collected included: total patient numbers assessed in the emergency room with a diagnosis of trauma; the mechanisms of trauma (blunt assault, motor vehicle accident, pedestrian vehicle accident, stab, gunshot wound, other); any trauma patient admitted to a health facility ward/ICU for longer than 12 h; and whether the patient required transfer to a higher centre of care. All trauma deaths in hospital were recorded. The severity of trauma was measured using the Emergency Medical Services (EMS) classification of blue code (dead), red code (stretcher case with deranged physiology), yellow code (stretcher case with normal physiology) and green code (able to walk with normal physiology. The DHIS trauma data from April 2012 to March 2014 was reviewed. Results: There were 197, 219 emergency room visits for trauma in KZN in the 2013/2014 financial year. This constitutes 27.0% of all emergency room visits. The ratio of intentional to non-intentional injury is 45:55. There were 18, 716 admissions to public sector hospitals for trauma in KZN in the 2013/2014 financial year. This constitutes 2.4% of all admissions in the province. There were 1045 inpatient deaths due to trauma in the same period, constituting 2.5% of all inpatient deaths. The overall rate of trauma in KZN was 17 per 1000 population. Conclusion: The adapted DHIS has successfully collected essential data that quantify the hospital burden of trauma in KZN province. This has provided the most complete overview of the burden of trauma in the Province. These trauma indicators should remain a permanent part of the DHIS to allow planners to track the trauma epidemic and to institute informed management strategies.